2017
DOI: 10.1016/j.neuropharm.2017.06.016
|View full text |Cite
|
Sign up to set email alerts
|

Atypical dopamine transporter inhibitors R-modafinil and JHW 007 differentially affect D2 autoreceptor neurotransmission and the firing rate of midbrain dopamine neurons

Abstract: Abuse of psychostimulants like cocaine that inhibit dopamine (DA) reuptake through the dopamine transporter (DAT) represents a major public health issue, however FDA-approved pharmacotherapies have yet to be developed. Recently a class of ligands termed “atypical DAT inhibitors” has gained attention due to their range of effectiveness in increasing extracellular dopamine (DA) levels without demonstrating significant abuse liability. These compounds not only hold promise as therapeutic agents to treat stimulant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 54 publications
(96 reference statements)
2
17
0
1
Order By: Relevance
“…Further, blockade of cocaine's enhancement of DA-mediated currents in DA neurons by JJC8-091 is consistent with our previous findings with similar compounds [26]. We previously showed that the benztropine analogue, JHW007, had little effect on its own but was able to blunt the cocaine-induced increase in DA currents, while R-modafinil alone enhanced DA currents and interacted in an additive manner with cocaine [26]. Similar findings were obtained here for JJC8-088, which appeared more cocaine-like, and JJC8-091, which dose-dependently inhibited the acute enhancement produced by cocaine in an even more efficacious manner than JHW007.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…Further, blockade of cocaine's enhancement of DA-mediated currents in DA neurons by JJC8-091 is consistent with our previous findings with similar compounds [26]. We previously showed that the benztropine analogue, JHW007, had little effect on its own but was able to blunt the cocaine-induced increase in DA currents, while R-modafinil alone enhanced DA currents and interacted in an additive manner with cocaine [26]. Similar findings were obtained here for JJC8-088, which appeared more cocaine-like, and JJC8-091, which dose-dependently inhibited the acute enhancement produced by cocaine in an even more efficacious manner than JHW007.…”
Section: Discussionsupporting
confidence: 92%
“…Also, JJC8-088, but not JJC8-091, produced significant cocaine-like effects on stimulus-elicited DA Max further suggesting a potential atypical profile for JJC8-091. Further, blockade of cocaine's enhancement of DA-mediated currents in DA neurons by JJC8-091 is consistent with our previous findings with similar compounds [26]. We previously showed that the benztropine analogue, JHW007, had little effect on its own but was able to blunt the cocaine-induced increase in DA currents, while R-modafinil alone enhanced DA currents and interacted in an additive manner with cocaine [26].…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…The classic atypical DAT inhibitor JHW 007 (benztropine-derived, not modafinil-derived) has been shown to effectively block cocaine and METH self-administration in rats (Hiranita et al , 2014, 2017). The off-target binding profile of both classes of drug are different and likely important for explaining the mechanism of action their effects (see for review, Avelar et al , 2017). One potentially relevant point of overlap is that the sigma-1/DAT binding ratio (0.24) for JJC8-089 (attenuated METH self-administration in LgA rats in the 6 h session) is equivalent to that of JHW 007 (0.20-0.23; Cao et al , 2016; Hiranita et al , 2017).…”
Section: Discussionmentioning
confidence: 99%